(x+4)(16 - 4x + x²) - x(x² + 8) = -192
Раскроем скобки
(x³ + 64) - x³ - 8x = -192 - мы преобразовали (x+4)(16 - 4x + x²) по формуле суммы кубов (a + b)(a² - ab + b²) = a³ + b³
-8x = -192 - 64
-8x = -256
x = 32
Ответ: 32
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
(x+4)(16 - 4x + x²) - x(x² + 8) = -192
Раскроем скобки
(x³ + 64) - x³ - 8x = -192 - мы преобразовали (x+4)(16 - 4x + x²) по формуле суммы кубов (a + b)(a² - ab + b²) = a³ + b³
-8x = -192 - 64
-8x = -256
x = 32
Ответ: 32